Optimization of biosurfactant production condition by thermophilic bacteria using waste frying oil / Nurul Fatihah Khairuddin - Khairuddin, Nurul Fatihah (2016)
Thermophilic biosurfactant-producer suitable for use in various industrial applications especially in microbial-enhanced oil recovery (MEOR) and the use of waste frying oil (WFO) as carbon source to synthesize biosurfactant has a potential prospect to decrease the production cost of biosurfactant and disposal of WFO. Thermophilic biosurfactan-tproducer isolated from Sungai Klah hot spring was investigated in this study. The isolated bacterium was characterized to be Anoxybacilus sp. by biochemical test and 16S ribotyping. The biosurfactant, which was produced by this bacterium, was able to lower the surface tension of nutrient broth with addition of 2% (v/v) of filtered diesel oil to 34.58 mN/m. Optimization of fermentation condition in this study involved four steps: screening for significant factors using 2³ full fractional factorial design (FFD), steepest ascent, optimization using face-centered central composite design (FCCD) and verification. Therefore, variations of three intresting parameters, WFO, sodium nitrate (NaNOs) and sodium chloride (NaCl) concentrations were selected for optimization conditions. The empirical model developed through response surface methodology (RSM) in term of effective operational factors was found to be adequate to describe the biosurfactant production. A maximum reduction in surface tension was obtained under the optimal conditions of 11.01% (v/v) WFO, 0.74% (w/v) NaN03 and 0.12% (w/v) NaCl. Thin layer chromatography (TLC) and Fourier transform infrared spectroscopy (FTIR) has been carried out to determine compositional analysis of the produced biosurfactant and it was characterized as lipopeptide (surfactin) derivative. The biosurfactant also was stable over wide range of temperature between 4°C to 121°C, pH ranging from 2 to 12 and salinity ranging from 0% (w/v) to 10% (w/v).